New Institutional Approach: The Construction of a Research Scheme - Radaev, Vadim (Journal of Economic Sociology, 2010)
The paper suggests a theoretical approach to the institutional analysis of the economic action. It begins with the discussion of the institutional approach specifics in economic sociology. After that a detailed research scheme is given and it combines institutional emergence, the structure of the economic actors’ motives and the concepts of control. The author highlights the forms of legitimate claims on the resources and incomes, the ways of keeping in touch, business networks and business strategies formation.